Resilience factors play an important role in the mental health of parents when children survive acute lymphoblastic leukaemia. (12th November 2015) - Eilertsen, Mary‐Elizabeth; Hjemdal, Odin; Le, Thien Thanh; Diseth, Trond H.; Reinfjell, Trude
Abstract: Aim: Childhood cancer is a tremendous stressor that requires parents to adapt to new challenges, and research has mainly focused on psychopathology and rarely on a resource‐oriented perspective, such as resilience. This study assessed resilience factors among parents of children surviving acute lymphoblastic leukaemia and parents of healthy children. We also explored the association between parental resilience and mental health. Methods: The study compared 57 parents of 40 children from eight to 15 years of age in remission from acute lymphoblastic leukaemia and 63 parents of 42 healthy children. The Resilience Scale for Adults and the General Health Questionnaire were used to assess parental resilience and mental health. Results: Parents of children surviving acute lymphoblastic leukaemia showed significantly lower levels of resilience than parents of healthy children, but no significant difference was found for mental health. Certain resilience factors were positively associated with mental health, especially for mothers, such as family cohesion, good perception of self and being able to plan their future. Conclusion: Resilience factors may help to protect parents' mental health, especially mothers, when their child has survived acute lymphoblastic leukaemia and should be considered in a clinical setting. Further research on resilience factors for fathers is needed.